Transition Towards Transradial Approach Improves Outcomes of Acute Myocardial Infarction PCI - Kalpak, Oliver; Donev, Doncho; Pejkov, Hristo; Antov, Slobodan; Kalpak, Gjorgji; Kedev, Sashko (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2017)
Introduction and aim: Transradial (TRA) instead of transfemoral (TFA) approach strategy has been presented in research literature as superior access strategy especially for acute ST elevation myocardial infarction (STEMI) primary percutaneous coronary intervention (PCI). There is a paucity of registry-based data of outcomes from default TRA strategy compared to TFA. Materials and methods: All-comers STEMI PCI institutional Registry identified 1808 consecutive patients in time-frame of 40 months from 2007 to 2010, without making any exclusions. Moreover, we applied Propensity Score Matching (PSM) to replace randomization, address the potential confounding and selection bias. PSM derived 565 congruent pairs of patients from the groups. Results: After 30 days the primary composite endpoint of major adverse cardiovascular events (MACE) was in favor of TRA 6.5% vs. 12.4% in TFA group, simultaneously secondary endpoints of death in TRA with rate of 4.8% and with rate of 10.1% in TFA. Moreover, the rate of major access related bleeding was 1.1% in TRA vs. 8.5% in TFA, in contrast the major non-access related bleeding was 1.8% and 2.4% respectively showed no significant difference. One year Kaplan Meier survival plots were in favor of TRA. Conclusions: Default transradial access strategy is associated with improved STEMI PCI outcomes.
Keywords: TRA; TFA; STEMI; acute myocardial infarction PCI; outcomes